The Nile : downriver through Egypt's past and present - Wilkinson, Toby A. H. (Bloomsbury, 2014)
Egypt is the most populous country in the world's most unstable region. It is the key to Middle East peace, the voice of the Arab world and the crossroads between Europe and Africa. Its historical and strategic importance is unparalleled. In short, Egypt matters. And the key to Egypt - its colourful past, chaotic present and uncertain future - is the Nile. From Herodotus's day to the present political upheavals, the steady flow of the Nile has been Egypt's heartbeat. It has shaped its geography, controlled its economy and moulded its civilisation. The same stretch of water which conveyed Pharaonic battleships, Ptolemaic grain ships, Roman troop-carriers and Victorian steamers today carries modern-day tourists past bankside settlements in which rural life - fishing, farming, flooding - continues much as it has for millennia. At this most critical juncture in the country's history, foremost Egyptologist Toby Wilkinson takes us on a journey up the Nile, north from Lake Victoria, from Cataract to Cataract, past the Aswan Dam, to the delta.